DOI: 10.31274/rtd-180816-3350
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting properties of Mg2Si single crystals

Abstract: LIST OF FIGURES Phase diagram of the magnesium-silicon system Graphite crucible used in preparation of MggSi single crystals Experimental arrangement for preparation of MggSi single crystals Sample holder for low-temperature measurements Apparatus for high-temperature measurements (a) sample holder (b) sample chamber and heater Temperature control for 77°-300°K (a) variable-height method (b) circulating-gas method Orientation of sample and probes Resistivity of n-type Mg^Si Resistivity of p-type MggSi Hall coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Morris (4) and Redin (2) in their work at Iowa State University found that an excess of silicon or an excess of germanium in an ingot does not affect the electrical properties of the Mg2Si or the Mg2Ge taken from the ingot. Morris in his work on single crystals of Mg2Si took his single crystals from ingots containing large amounts of excess silicon.…”
Section: Thermoelectric Figure Of Meritmentioning
confidence: 99%
“…Morris (4) and Redin (2) in their work at Iowa State University found that an excess of silicon or an excess of germanium in an ingot does not affect the electrical properties of the Mg2Si or the Mg2Ge taken from the ingot. Morris in his work on single crystals of Mg2Si took his single crystals from ingots containing large amounts of excess silicon.…”
Section: Thermoelectric Figure Of Meritmentioning
confidence: 99%
“…Mg2Sioriented thermoelectric materials are promising within 500 to 900 K. This is because of immense attainment in the values of ZT to 1.3 [25,26,27]. Because of the extreme closeness in the boiling value of magnesium and the melting value of Mg2Si, treatment of Mg2Si is not easy [28]. Method like spark plasma and ball-milling are therefore employed to synthesize Mg2Si.…”
Section: Thermoelectric Materials (Mg2si)mentioning
confidence: 99%
“…For single-crystal Mg2Si growth, the VB [8] and vertical gradient freeze (VGF) methods [9] are used in a closed-tube system, where a crucible containing the raw materials is encapsulated in a closed ampoule with an Ar pressure of approximately 2-3 atm, to prevent Mg evaporation during crystal growth [1,3,[10][11][12]. Recently, 18-mm diameter Mg2Si single crystals without small-angle grain boundaries were synthesized by the VB method using a closed-tube system and a boron nitride (BN)-coated pyrolytic boron nitride (pBN) crucible [13].…”
Section: Introductionmentioning
confidence: 99%